Analisis Prioritas Anggaran Program Pada Dinas Pendidikan Kota Banjarmasin - Safitri, Sukma Rani; Nur, Muhamad Anshar (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This research was (1) find out the criteria that determine priority budget programs Banjarmasin City Education Office, (2) find out alternative program options Banjarmasin City Education Office, (3) find out priority budget program preferences Banjarmasin City Education Office. The respondents, 9 respondents were influential in determining priority programs on budget for the Banjarmasin City Education Office using the AHP method. The results of this study indicate that alternatives criteria from HR availability, targeting, availability of funds, and benefits on the choice of priority budget programs Banjarmasin City Education Office with a preference of availability of funds 47%, benefits 28%, HR availability of 16%, and targeting 9%. Based on these alternative criteria, choices were obtained with the priority order of programs education management 44%, teaching staff and education 29%, curriculum development 18%, and education licensing control 9%. that the most prioritized is the education management program by 44%.